Mengeksplorasi Motivasi Siswa Introvert dalam Pembelajaran Bahasa Inggris di SMA Yadika Langowan - S. Reppie, Jhonatan; P. Warouw, Maya; R. Lotulung, Donald (Universitas Andalas, 2025)
This study explores the motivation of introverted students in learning English at SMA Yadika Langowan. The purpose of this study is to describe the influence of introverted traits on learning motivation as well as to identify factors that motivate introverted students in learning English. This research uses a qualitative method with a case study approach as proposed by Creswell. In addition, this study uses Albert Bandura's Social Cognitive Theory to analyze learning motivation and Carl Gustav Jung's personality theory to identify the characteristics of introverted students. The research data were taken from 4 introverted students at SMA Yadika Langowan. The results show that firstly introverted students tend to be more comfortable learning independently, and their level of confidence depends on their understanding of the material. Secondly, internal and external factors also play a role in motivating introverted students. The internal factors include self-efficacy, preference for independence, learning goals, and encouragement to get out of their comfort zone. The external factors include environmental factors, social support, comments, and judgment, as well as the presence of role models, which play an important role in increasing introverted students' learning motivation. The findings provide insights into learning strategies that are more suitable for introverted students in English language learning.